Structure and Physical Properties of 30MgSO4-(70-x) P2O5-xSm2O3 glasses - Mohammed Aliyu, Aliyu; Ahmed, N E (EDUCATUM Journal of Science, Mathematics and Technology, 2019)
Glasses in the series 30MgSO4-(70-x) P2O5-xSm2O3 0.2  x 1.0 mol percent were prepared by single step melt-quench techniques, the structure, physical and optical properties of samarium oxide at different concentrations were studied. The amorphous phase of the samples was verified by X-ray diffraction spectroscopy, the structural units were investigated using Fourier Transform Infrared, Raman and NMR spectroscopy where the spectra reveal the presence of symmetric, asymmetric, torsoional and bending vibration of phosphate groups, the NMR spectra reveals the changes in Qn distribution here discussed, the compositional dependence on physical (density, average molar weight, dielectric constant, Inter-nuclear distance, Field strength, Molar volume, Molar refractivity etc) and optical parameters were determined. In terms of structural modifications, there is variation of density and molar volume, the glass sample has increasing refractive index values with decreasing molar volume content. The luminescence spectra were observed within UV-Vis-NIR region, the absorption spectra of the sample were recorded in the range of 350 to 1800 nm meanwhile, absorption edge the optical band-gap, and E was evaluated. Our result may be advantageous for many optical applications (e.g visible lasers or color displays).